A Bioarchaeological and Biogeochemical Study of Warfare and Mobility in Andahuaylas, Peru (ca. ad 1160–1260). (19th March 2014) - Kurin, D. S.; Lofaro, E. M.; Gómez Choque, D. E.; Krigbaum, J.
Abstract: Warfare impacts how people and populations can move about the landscape. Ethnographers have posited that internal warfare, conflict that takes place within a single society, is strongly associated with female abduction. In contrast, external warfare, combat between different societies, is often accompanied by the in‐migration of men for purposes of defence. To test this assertion, we evaluate human remains from one of the most violent eras in Andean prehistory, the Late Intermediate Period (ad 1000–1400). In the south‐central highlands of Andahuaylas, Peru, this era witnessed the coalescence of two formidable polities, the Chanka and the Quichua. Ethnohistoric accounts describe internal warfare among the Chanka and external warfare between the Quichua and their neighbours. In this study, bioarchaeological and biogeochemical methods are marshalled to elucidate ancient patterns of violence and mobility with greater nuance. We employ strontium isotope analysis of tooth enamel apatite to inform on residential origin, and we reconstruct patterns of violent conflict through analysis of cranial trauma. In all, 265 crania were excavated from 17 cave ossuaries at two Chanka sites and one Quichua site. Data were collected on age, sex and cranial modification—an indicator of social identity and cranial trauma. A representative subsample of molars from 34 individuals subjected to strontium isotope analysis demonstrates that among the Chanka, violence was significantly directed towards social groups within society, marked by modified crania. The presence of two nonlocal women with signs of increased morbidity and mistreatment points to possible mobility‐by‐abduction. In contrast, among the Quichua, men have significantly more trauma, and wounds are concentrated on the anterior. Trauma on women is lower, nonlethal, and concentrated on the posterior. This divergent pattern is commonly observed in external warfare (raids and community defence), where men face attackers and women escape them. The presence of two nonlocal men supports a mobility model of strategic in‐migration. In sum, osteological and isotopic data sets are shown to reveal divergent life‐course experiences not captured by the archaeological data or historic records alone. Copyright © 2014 John Wiley & Sons, Ltd.